The relationship between socio-demographic characteristics with genital self-image in the women, 2016 - Mina Sabbaghan; Mozhgan Mirghafourvand; Sevil Hakimi; Jamileh Malakouti (Golestan University of Medical Sciences, 2021)
Background: Genital self-image could express an individual's attitudes towards her feelings-thoughts and changes in her behavior in a variety of conditions positively or negatively. This study aimed to determine the relationship between socio-demographic characteristics with the genital self-image in women referred to Health Care Centers. Methods: This cross-sectional study was performed on 239 women between 18-40 years old in 5 health care centers of Qazvin, by convenience sampling method in 2015-2016. Data were gathered using the research-made questionnaire of genital self-image set by the researcher. Independent t-test, one-way ANOVA, and general linear model were used to analyze data. Data were analyzed using SPSS 16. Results: The mean score (SD) of the genital self-image in participants was 53.4 (12.1) from the total range of 0-100. Most women (83.7%) had moderate, 9.2% good and 7.1% poor genital self-image, respectively. There was a significant statistical relationship between the variables of occupation, woman and her husband's education levels, and body mass index with genital self-image (P<0.05). Conclusion: Only a small number of women had a good genital self-image. Therefore, concerning the adverse and inappropriate consequences of genital self-image, it is recommended to study the other factors affecting genital self-image.